Loss of Basal Forebrain Cholinergic Neurons Following Adolescent Binge Ethanol Exposure: Recovery With the Cholinesterase Inhibitor Galantamine - Crews, Fulton T.; Fisher, Rachael; Deason, Chloe; Vetreno, Ryan P. (Frontiers in Behavioral Neuroscience, 2021)
Binge drinking and alcohol abuse are common during adolescence and cause both cognitive deficits and lasting cholinergic pathology in the adult basal forebrain. Acetylcholine is anti-inflammatory and studies using the preclinical adolescent intermittent ethanol (AIE; 5.0 g/kg, i.g., 2 day on/2 day off from postnatal day [P]25 to P54) model of human adolescent binge drinking report decreased basal forebrain cholinergic neurons (BFCNs) and induction of proinflammatory genes that persist long into adulthood. Recent studies link AIE-induced neuroimmune activation to cholinergic pathology, but the underlying mechanisms contributing to the persistent loss of BFCNs are unknown. We report that treatment with the cholinesterase inhibitor galantamine (4.0 mg/kg, i.p.) administered during AIE (i.e., P25 – P54) or following the conclusion of AIE (i.e., P57 – P72) recovered the persistent loss of cholinergic neuron phenotype markers (i.e., ChAT, TrkA, and p75NTR) and somal shrinkage of residual ChAT+ neurons known to persist in AIE-exposed adults. Galantamine treatment also recovered the AIE-increased expression of the proinflammatory receptors TLR4 and RAGE, the endogenous TLR4/RAGE agonist HMGB1, and the transcription activation marker pNF-kappa B p65. Interestingly, we find BFCNs express TLR4 and RAGE, and that AIE treatment increased pNF-kappa B p65 expression in adult ChAT+IR neurons, consistent with intracellular HMGB1-TLR4/RAGE signaling within BFCNs. AIE increased epigenetic transcription silencing markers (i.e., H3K9me2 and H3K9me3) in the adult basal forebrain and H3K9me2 occupancy at cholinergic phenotype gene promoters (i.e., ChAT and TrkA). The finding of no AIE-induced changes in total basal forebrain NeuN+ neurons with galantamine reversal of AIE-induced ChAT+ neuron loss, TLR4/RAGE-pNF-kappa B p65 signals, and epigenetic transcription silencing markers suggests that AIE does not cause cell death, but rather the loss of the cholinergic phenotype. Together, these data suggest that AIE induces HMGB1-TLR4/RAGE-pNF-kappa B p65 signals, causing the loss of cholinergic phenotype (i.e., ChAT, TrkA, and p75NTR) through epigenetic histone transcription silencing that result in the loss of the BFCN phenotype that can be prevented and restored by galantamine.